ROLE OF INTERNET IN KNOWLEDGE MANAGEMENT - Dr. S. M. Abbas, Dr. Sanjeev Kumar Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Internet plays an important role globally. It works on the basis of standard protocols. With the evolution of web 4.0, a paradigm shift has been observed in applying the technologies especially internet, which allows to access large number of content pages of our need. Knowledge sharing, transferring, transmitting has become very easy in organizations. This is possible through the use of internet by which a large number of files transfer within moment. Internet also plays a key role for managing knowledge in organizations.